UMNO party elections: incumbents in control, for the moment - Hamdan, Shahril (2023)
The UMNO party elections held soon after Malaysia’s 15th General Election (GE15) were framed as a test of how its members felt about recent events. These included a prolonged period of internal wrangling, UMNO’s worst electoral showing in history leading to an alliance in government with old foes, a decision not to contest the top two party posts, and an internal purge of a handful of erstwhile aspirants to top leadership positions. The results show that, for the moment, UMNO members are content to fall in line behind the current leadership, although capacity for change remains.